The Customer as an Accounting Entity - Bochenek, Magdalena (Klient jako podmiot rachunkowości, 2022)
The aim of the article was to present the customer as an accounting entity. The article describes the growing role of the customer in company management. Businesses are increasingly customer-oriented, and this also results in a customer orientation of management accounting methods which can be used to measure customer costs and customer value. The results of the research on customer orientation of enterprises are discussed. The research was conducted among enterprises based in the Podkarpackie region with more than 49 employees. The results confirmed that the employees consider their customers to be important as they generate the most revenue. In contrast, a relatively small number of respondents identified customers as the people through whom the enterprise incurs costs and achieves economic success., whereas most entrepreneurs perceive customers only from the revenue side. The research methods used in the article are a critical analysis of the literature and a quantitative method, which consisted of direct research using the questionnaire technique.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 1-13
Keywords: customer; customer value; customer costs; cost accounting; management accounting; klient; wartość klienta; koszty klienta; rachunek kosztów; rachunkowość zarządcza